2017
DOI: 10.1136/bmjgast-2017-000155
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and screening for anaemia in mild to moderate Crohn's disease and ulcerative colitis in the United States, 2010–2014

Abstract: Background and aimsAnaemia affects up to 74% patients with Crohn's disease (CD) and ulcerative colitis (UC) and is correlated with decreased quality of life. The European Crohn's and Colitis Organisation (ECCO) recommends at least annual screening for iron-deficiency anaemia. We aimed to determine the prevalence of anaemia, frequency of anaemia screening and factors associated with anaemia in a retrospective study of mild to moderate inflammatory bowel disease (IBD) in the USA.MethodsAdults with at least two o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…Inflammatory bowel disease affects over 1.5 million Americans, and effective treatment options for this debilitating autoimmune disorder are lacking ( 21 ). While anti-TNF therapies have proved efficacious in certain patient populations, more therapeutic approaches are clearly needed ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory bowel disease affects over 1.5 million Americans, and effective treatment options for this debilitating autoimmune disorder are lacking ( 21 ). While anti-TNF therapies have proved efficacious in certain patient populations, more therapeutic approaches are clearly needed ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for anemia included extensive disease in case of UC and penetrating or colonic disease in case of CD. In a study, from the USA, which included 17,059 adults with IBD, the prevalence of anemia was 32.4% in CD and 27.6% in UC [ 139 ]. It was attributed to iron deficiency in 79.2% of those with CD and 85.1% of those with UC.…”
Section: The Asian Working Group Guidelines Regarding Diet In Inflammmentioning
confidence: 99%
“…Patients with IBD are at increased risk of micronutrient deficiency (including folate, iron, magnesium, vitamin B 12 , calcium, phosphate) due to reduced intake of nutrients secondary to anorexia, malabsorption (inflamed mucosa or short bowel after surgical resection), increased losses (fistulae, exudation in gastrointestinal tract), and effect of drugs used in the treatment of IBD [ 158 , 159 ]. Iron deficiency is the most common cause of anemia in IBD patients [ 138 , 139 , 160 ]. In addition to reduced intake due to anorexia and increased GI losses, impaired iron metabolism contributes to an iron deficient state in IBD.…”
Section: The Asian Working Group Guidelines Regarding Diet In Inflammmentioning
confidence: 99%
“…Previous studies of accuracy of diagnostic codes in the USA found that 67.5% of patients with CD were correctly classified based on at least one ICD-9-CM 555 encounter3 and 88% with two encounters 4. Some cohorts have not performed their own validation studies; rather, they have relied on a case definition of two encounters based on prior evidence 5–10. One study showed a positive predictive value (PPV) of 91% when a CD code was present without any UC codes, although this appears to be an outlier 11.…”
Section: Introductionmentioning
confidence: 99%